Development of Creativity and Academic Achievement in Computer Subjects Using a Problem-Based Learning Management Model for Mathayom 1 Students - Khochakul, Arthitaya; Naka, Songkram (Journal of Buddhist Education and Research (JBER), 2025)
This research aimed to develop creativity in terms of fluency, flexibility, initiative, and refinement in computer studies among Mathayom 1 students by using a problem-based learning management model, to compare their academic achievement before and after learning through the model, and to study their satisfaction with this learning approach. The sample group consisted of 30 Mathayom 1 students from Nong Yai Municipality School, Khon Kaen Municipality, selected through cluster random sampling. The research instruments included eight lesson plans on learning to use Microsoft Word, a creativity assessment form as a performance task, an academic achievement test with 20 multiple-choice questions, and a satisfaction questionnaire with 15 items using a five-point rating scale. The data were analyzed using mean, standard deviation, percentage, and the dependent samples t-test. The research findings revealed that 26 students (86.67%) achieved creativity scores of not less than 70 percent, meeting the set criteria, while 4 students (13.33%) did not. The order of creativity components from highest to lowest was fluency, flexibility, initiative, and refinement. The learning achievement of students who studied through the problem-based learning management model was significantly higher after instruction than before, at the .05 level of significance. The students’ overall satisfaction with learning through the model was at a high level (𝑥̅ = 4.33, S.D. = 0.69).